Evaluation of nursing preceptorship programs in hospital settings: A scoping review - Rajagukguk, Eva Suryanti; Manalu, Enjelika Putri; Pajuk, Erica Dorellia; Sinurat, Kyela Friska Br; Eka, Ni Gusti Ayu (Malahayati International Journal of Nursing and Health Science, 2026)
Background: The quality of nursing services within healthcare institutions is closely linked to the competence of nurses. Competence development is strongly supported by structured and effective mentoring, which facilitates the clinical adaptation of newly graduated nurses. Through preceptorship, novice nurses gain opportunities to integrate into clinical practice, while preceptors serve as role models and supervisors, guiding the professional growth of their mentees. Evaluating the implementation of preceptorship programs is essential to assess both the mentoring process and the experiences of preceptors and preceptees. Such evaluations provide valuable insights for strengthening and advancing preceptorship initiatives in hospital settings. Purpose: To evaluate the implementation of preceptorship programs in hospitals. Method: A scoping review was conducted, involving a comprehensive search of electronic databases such as PubMed, MEDLINE (via EBSCO), and ScienceDirect (Elsevier). The search strategy employed relevant keywords and MeSH terms related to nursing, preceptorship programs, and hospital contexts. Data extraction emphasized outcomes associated with program effectiveness, and the findings were synthesized through descriptive and narrative approaches, integrating both quantitative and qualitative evidence. Results: Preceptorship programs facilitate the adaptation of novice nurses by enhancing clinical skills, confidence, and professional identity, while contributing to nurse retention and improved quality of care. However, challenges such as preceptor workload and limited institutional support remain. Overall, preceptorship demonstrates positive impacts, though issues of sustainability and standardization require further attention. Conclusion: Preceptorship plays a significant role in strengthening nurse competence and improving organizational outcomes. Nevertheless, ensuring sustainability and establishing standardized frameworks are critical for optimizing its long-term effectiveness.